2010
DOI: 10.4314/sljbr.v2i1.56600
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Hepatitis B Surface Antigen (HBsAg) among Children of Primary School Age in a Community, North-Central, Nigeria

Abstract: Globally, Hepatitis B Virus has been identified as one of the most common infectious diseases and a major public health problem.This study was therefore carried out to assess the prevalence of Hepatitis B virus infection among primary school children attending LGE primary school, Sabon Pegi, Kuru, Nigeria. Three hundred and sixty (360) blood samples were collected from the pupils and sera separated and analyzed for HBsAg using one step Hepatitis B surface antigen test strip. Of the 360 samples screened, 35 (9.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 18 publications
2
17
4
Order By: Relevance
“…This implies that the two genders were exposed to different possible predisposing factor(s) to HBV transmission in the environment and that is most probably the practice of circumcision by traditional healers which is generally decreasing among the female children in Nigeria. 13 This is corroborated by the findings by Ndako et al 11 from North-Central Nigeria, Kiire CF from sub-Saharan Africa and Ayoola et al who demonstrated higher HBsAg sero-prevalence among male children who had circumcision by traditional healers. 14,15,16 The role of the universal HBV vaccination in the prevention against and/or reduction in the incidence and prevalence of HBV infection has been well documented in the literature.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…This implies that the two genders were exposed to different possible predisposing factor(s) to HBV transmission in the environment and that is most probably the practice of circumcision by traditional healers which is generally decreasing among the female children in Nigeria. 13 This is corroborated by the findings by Ndako et al 11 from North-Central Nigeria, Kiire CF from sub-Saharan Africa and Ayoola et al who demonstrated higher HBsAg sero-prevalence among male children who had circumcision by traditional healers. 14,15,16 The role of the universal HBV vaccination in the prevention against and/or reduction in the incidence and prevalence of HBV infection has been well documented in the literature.…”
Section: Resultssupporting
confidence: 79%
“…Male gender had been identified as an important risk factor for the transmission of HBV infection in previous studies. 8,11,12 However, the figure (23.3%) obtained in this study is higher than 9.7% among primary schoolchildren from Kuru, This difference may be a reflection of the environments as this study was conducted in a rural area where the burden of HBV infection is said to be higher. 10 Conversely, the finding of statistically significant (p< 0.005) higher HBsAg sero-positivity among the male subjects (15.8%) compared to their female counterparts (7.8%) in this study was in agreement with the findings of Bukbuk et al 8 from Borno and Gogos et al 12 from Greece who reported higher prevalence rates among male subjects screened.…”
Section: Resultscontrasting
confidence: 45%
See 1 more Smart Citation
“…1 The infection is hyper-endemic in Nigeria with prevalence rates of the HB surface antigen (HBsAg) varying in different segments of the population. [2][3][4][5][6] The HBsAg prevalence rate was 11% amongst pregnant women, 2 17% in female sex workers 3 and 15% in a low-risk blood donor group. 4 In children, without the human immunodeficiency virus (HIV), the HBsAg prevalence was 9% 5,6 and 19% in those who had HIV.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] The HBsAg prevalence rate was 11% amongst pregnant women, 2 17% in female sex workers 3 and 15% in a low-risk blood donor group. 4 In children, without the human immunodeficiency virus (HIV), the HBsAg prevalence was 9% 5,6 and 19% in those who had HIV. 6 Hepatitis B infection is preventable through vaccination.…”
Section: Introductionmentioning
confidence: 99%